Rational utilization of intramolecular and intermolecular hydrogen bonds to achieve desirable electron transporting materials with high mobility and high triplet energy. Issue 7 (22nd January 2016) - Yin, Xiaojun; Chen, Dongcheng; Peng, Qiming; Xiang, Yepeng; Xie, Guohua; Zhu, Zece; Zhong, Cheng; Li, Feng; Su, Shijian; Yang, Chuluo
Abstract : New pyrimidine-containing triazine-cored compounds showed high E T and high μ e by utilizing intramolecular and intermolecular hydrogen bonds. Abstract : Three new pyrimidine-containing star-shaped compounds, namely, 1, 3, 5-tri(3-(pyrimidin-5-yl)phenyl)benzene (TPM-TPB ), 2, 4, 6-tris(3-(pyrimidin-5-yl)phenyl)-1, 3, 5-triazine (TPM-TAZ ) and 3, 5, 6-tris(3-(pyrimidin-5-yl)phenyl)-1, 2, 4-triazine (TPM-i-TAZ ), were synthesized and characterized. These new compounds exhibited favorable electronic affinity ( E a >2.81 eV) and the triplet energy levels ( E T ) up to ∼2.83 eV. X-ray diffraction analysis of the compounds revealed that the intramolecular and intermolecular C–H⋯N hydrogen bonds ofTPM-TAZ resulted in high electron mobility up to 2.0 × 10 −3 cm 2 V −1 s −1 . Using these compounds as the electron transporting materials, the blue phosphorescent organic light-emitting devices showed good performance, with a very low turn-on voltage of 2.4 V, a maximum current efficiency of 26.4 cd A −1, and a maximum power efficiency of 26.9 lm W −1 .